Liquidity – Profitability Trade-Off on the Example of Companies Listed on Main and Alternative New Connect Markets on Warsaw Stock Exchange - Bolek, Monika; Pluskota, Anna; Wolski, Rafał (Journal of Finance and Financial Law, 2020)
The goal of this paper is related to the liquidity and profitability relationship analysis and their maxima assessment in the companies listed in the main and alternative markets of Warsaw Stock Exchange. The trade-off between maximum profitability and liquidity is the result of value maximization and bankruptcy prevention strategies and this approach is expected to be similar in all listed companies due to investors’ expectation. It has been found that there is no difference in management goals in the markets taken into consideration and companies in both research samples maximize profitability within a conservative approach to the liquidity. The maximum liquidity, on the other hand, is determined with a similar level of profitability as measured by ROE on the main market of WSE and NewConnect.